Temporal and geographical dynamics of early-onset Parkinson’s disease burden: insights from the Global Burden of Disease Study 2021 - Yong Li; Dianhui Tan; Cheng Luo; Junchen Chen (Frontiers in Neurology)
IntroductionEarly-onset Parkinson’s disease (EOPD) is a rare degenerative condition of the nervous system that primarily affects individuals of working age. Its distinct clinical and genetic features make it a critical area of study in neurological research and public health.Methods and materialsThis analysis utilized data from the Global Burden of Disease Study 2021, covering 371 diseases and injuries across 204 countries and territories from 1990 to 2021. The study focused on individuals aged 15–49 to characterize EOPD. Data on occurrence, frequency, mortality, and disability-adjusted life years (DALYs) were collected. Sociodemographic measures were used to analyze patterns and differences. Statistical methods, including joinpoint regression and decomposition analysis, were employed to identify temporal patterns and factors influencing variations in EOPD burden over time.ResultsThe global incidence of EOPD saw a significant increase between 2000 and 2009, with an average annual percentage change (AAPC) of 4.3%, continuing at a slower rate (AAPC 1.6%) from 2010 to 2021. By 2021, the incidence reached 2.1 cases per 100,000 population, up from 1.0 in 1990. Males had a higher incidence (AAPC 2.3%) compared to females (AAPC 0.8%). In 2021, 59.7% of the 81,047 global EOPD cases were male. Significant increases were observed in East Asia (AAPC 5.1%), Andean Latin America (AAPC 2.0%), and North Africa/Middle East (AAPC 1.1%), with a decline in High-income North America. China had the highest incidence in 2021 (5.17 cases per 100,000), followed by Peru and Bolivia. Saudi Arabia had the highest DALYs attributable to EOPD. The decomposition study indicated that the rise in global incidence and DALYs from 1990 to 2021 was mainly driven by epidemiological changes and population growth, with regional variations in impact.ConclusionThis global analysis highlights the need for targeted interventions and research to address gender-specific risk factors, regional disparities, and the effects of epidemiological changes on the growing EOPD burden.